PERAN BUDAYA KEUANGAN DALAM MEMEDIASI PENGARUH KEARIFAN LOKAL TERHADAP PENGENTASAN KEMISKINAN - Abu Bakar; Longginus Gelatan; Siske Tontong; Muh. Al-Azhar Jamaluddin (Center for Economic Studies Universitas Katolik Parahyangan, 2026)
The increasing poverty rate in Mimika Regency indicates that the wealth of natural resources, particularly from the mining sector, has not significantly impacted the welfare of the community, especially the Amungme and Kamoro tribes as indigenous people. This condition reflects the limitations of conventional development models that do not integrate local wisdom with the modern economic system that tends to be individualistic. In fact, local wisdom has the potential to support sustainable resource management, but is often marginalized by the dominance of market logic. Therefore, this study is relevant to examine the role of financial culture as a bridge in transforming local values ​​into a more inclusive poverty alleviation strategy. This study aims to analyze the influence of local wisdom on poverty alleviation and examine the role of financial culture as a mediating variable. The research method used explanatory research with a quantitative approach through the distribution of questionnaires to 100 respondents selected purposively. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results showed that local wisdom significantly influences financial culture, but does not directly influence poverty alleviation. Conversely, financial culture significantly influences poverty alleviation and is proven to mediate the relationship between local wisdom and poverty alleviation. These findings emphasize the importance of internalizing local wisdom through sound financial practices as the basis for a more effective, inclusive, and sustainable poverty alleviation strategy.